A Dy-MOF fluorescent probe material, its preparation method and application

By developing Dy-MOF fluorescent probe materials, the problem of the existing technology being difficult to detect chromium ions in water quickly and accurately is solved, and high sensitivity, stability and anti-interference detection of Cr3+ is achieved, and the preparation method is economical and environmentally friendly.

CN116496507BActive Publication Date: 2025-03-14CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310590994.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2025-03-14
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

The prior art is difficult to quickly, accurately and efficiently detect chromium ions in water, especially trivalent chromium and hexavalent chromium. Excessive amounts of these chromium ions will pose a serious threat to human health and ecological environment.

Method used

A Dy-MOF fluorescent probe material with a structural formula of [Dy(L)3(H2O)3]n·2nH2O. By synthesizing the molar ratio of 4-(3,5-dimethyl-1H-pyrazole-1-yl)benzoic acid to dysprosium salt is 3:2 to 2:3, Dy-MOF fluorescent probe material with high fluorescence intensity and stability is prepared for detecting Cr3+ in water.

Benefits of technology

The Dy-MOF fluorescent probe material exhibits strong sensitivity, stability, anti-interference and recyclability, and can quickly and accurately detect Cr3+ in water. It has a simple preparation method, low cost, low pollution and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004245503500000011
    Figure HDA0004245503500000011
  • Figure HDA0004245503500000012
    Figure HDA0004245503500000012
  • Figure HDA0004245503500000021
    Figure HDA0004245503500000021
Patent Text Reader

Abstract

The present invention belongs to the technical field of fluorescent sensors, and specifically relates to a Dy-MOF fluorescent probe material and a preparation method and application thereof. The structural formula of the fluorescent probe material is [Dy(L)3(H2O)3] n ·2nH2O, wherein the ligand is 4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid. The preparation method of the Dy-MOF fluorescent probe material comprises: uniformly mixing the ligand 4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid, KOH, dysprosium salt, methanol and H2O, volatilizing at room temperature, filtering and drying to obtain the metal coordination polymer. The Dy-MOF fluorescent probe material has good fluorescence stability and can highly selectively identify Cr in the solution. 3+ Ions have strong stability and anti-interference ability and can be reused. In addition, the preparation method is simple, and has the advantages of easy operation, high yield and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fluorescence sensors, and in particular relates to a Dy-MOF fluorescent probe material and a preparation method and application thereof. Background Art

[0002] With the rapid development of economy and the acceleration of industrialization, the pollution of domestic water and industrial wastewater has become increasingly serious, endangering people's health and safety. Therefore, monitoring of pollutants has become an important means to protect the ecology and people's health. Chromium is a blue-white multivalent metal element, and the common ones are divalent chromium, trivalent chromium and hexavalent chromium. Metallic chromium is hard and brittle, and resistant to corrosion, so it is often used in stainless steel and other products. At the same time, chromium is also a trace element necessary for the human body, but excessive intake of chromium is very harmful to the human body. Its toxicity is related to the valence state. The toxicity of divalent chromium is very mild, while the toxicity of trivalent chromium is easy to show in the human body. Long-term and large-scale intake of trivalent chromium will affect the body's antioxidant system on the one hand, making it easy to get some chronic oxidative diseases, such as diabetes and hypertension. On the other hand, due to the damage of the antioxidant system, it is easy to develop abnormal proliferative diseases such as tumors. Compared with trivalent chromium, hexavalent chromium is more toxic, about 100 times that of trivalent chromium. Clinically, the harm of hexavalent chromium and its compounds to the human body usually manifests in three aspects: damage to the skin, causing dermatitis, etc.; damage to the respiratory system, causing pneumonia, tracheitis and other diseases; damage to the digestive system, causing gastritis, gastric ulcers and intestinal ulcers, and severe cases can also lead to renal failure and even cancer. The fluorescence sensing method mainly achieves qualitative and quantitative analysis by quenching or enhancing the fluorescence of the probe material after adding the object to be detected. Coordination polymers have the advantages of diverse topological structures, high porosity, adjustable pore size, and excellent fluorescence properties, making them an important component of fluorescent probe materials. They show the advantages of high selectivity and high sensitivity in fluorescent identification of different types of analytes such as metal ions, organic small molecules, and biological molecules. Therefore, it is an urgent problem to develop a coordination polymer with fluorescence sensing properties that can be used for rapid, accurate and efficient detection of chromium. Summary of the invention

[0003] The present invention aims to provide a Dy-MOF fluorescent probe material and a preparation method and application thereof. The fluorescent probe material is used to detect Cr in water. 3+ The detection shows strong sensitivity, stability, anti-interference and recyclability, and the preparation method of the fluorescent probe material is simple, low cost, low pollution and easy to operate.

[0004] The technical solution adopted by the present invention is:

[0005] Dy-MOF fluorescent probe material, its structural formula is: [Dy(L)3(H2O)3] n·2nH2O, L in the structural formula - =4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid anion; crystallized in the triclinic Pī space group with Z=2, unit cell parameters: α=85.172(19)°, β=76.808(17)°, γ=82.862(18)°.

[0006] The preparation method of the above-mentioned Dy-MOF fluorescent probe material comprises the following steps:

[0007] (i) respectively measuring deionized water and KOH, and mixing them to prepare a KOH solution;

[0008] (ii) Weigh the ligand 4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid (HL), add it to the KOH solution and methanol prepared in step (i), dissolve and stir to obtain a yellow clear solution;

[0009] (iii) dissolving the dysprosium salt in deionized water at room temperature, and then slowly adding it dropwise to the yellow clear solution of step (ii) to obtain an orange-yellow transparent solution, which evaporates at room temperature to obtain light yellow needle-shaped crystals;

[0010] (iv) filtering, washing, drying and grinding the light yellow needle-shaped crystals obtained in step (iii) to obtain a Dy-MOF fluorescent probe material.

[0011] The molar ratio of the ligand HL to the dysprosium salt is 3:2 to 2:3.

[0012] Preferably, the molar ratio of the ligand HL to KOH is 1:1 to 1:1.5.

[0013] Preferably, the mass fraction of the solute in the KOH solution in step (i) is 0.3%.

[0014] Preferably, the dissolving and stirring time in step (ii) is 30 to 60 minutes.

[0015] Preferably, the dysprosium salt in step (iii) is any one of dysprosium nitrate pentahydrate or dysprosium chloride hexahydrate.

[0016] Preferably, the pore size of the filter membrane used in the filtration described in step (iv) is 22 μm.

[0017] Preferably, the solvent used for washing in step (iv) is a mixed solution of deionized water and DMF in a volume ratio of 1:1 to 3:1, and the number of washing times is 2 to 3 times.

[0018] Preferably, the drying temperature in step (iv) is 60-80° C., and the drying time is 8-12 hours.

[0019] Preferably, the grinding in step (iv) is performed using an agate mortar for 30 to 60 minutes.

[0020] The above Dy-MOF fluorescent probe material is used to detect Cr in water 3+ .

[0021] The specific operation method is as follows:

[0022] The Dy-MOF fluorescent probe material is ground, dispersed in deionized water, and prepared into a suspension by ultrasonic treatment, and then a Cr-containing 3+ The liquid sample to be tested is then excited for fluorescence and the wavelength of the fluorescence emission is tested and analyzed.

[0023] Preferably, the Dy-MOF fluorescent probe material is ground into 60-80 mesh.

[0024] Preferably, Dy-MOF is prepared into a suspension with a concentration of 0.01 M, and the ultrasonic treatment time is 30-60 min.

[0025] Preferably, containing Cr 3+ The concentration of the liquid sample to be tested is 0~0.36mM; 3+ The liquid sample to be tested is ultrasonically dissolved with chromium nitrate and deionized water for 30 to 60 minutes to obtain a chromium nitrate solution.

[0026] Compared with the prior art, the Dy-MOF fluorescent probe material synthesized with 4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid as a ligand has higher fluorescence intensity and stability, and the Dy-MOF fluorescent probe has the selective recognition of Cr 3+ Compared with the existing detection methods, it shows stronger sensitivity, stability, anti-interference and recyclability, and the preparation method is simple, recyclable, low cost, low pollution and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 One-dimensional chain structure diagram of the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention;

[0028] Figure 2 Infrared spectrum of the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention;

[0029] Figure 3 PXRD pattern of the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention;

[0030] Figure 4 TGA graph of the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention;

[0031] Figure 5 Fluorescence emission spectrum of the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention;

[0032] Figure 6 Comparison of fluorescence intensities of the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention after adding various ions;

[0033] Figure 7 The Dy-MOF fluorescent probe material prepared in Example 1 of the present invention is effective for different concentrations of Cr 3+ Fluorescence response spectrum of

[0034] Figure 8 The Dy-MOF fluorescent probe material prepared in Example 1 of the present invention is effective for Cr in the presence of various interfering metal ions. 3+ Fluorescence response intensity diagram of anti-interference test of ion detection;

[0035] Fig. 9 The fluorescence intensity ratio of the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention based on the SV equation is 3+ Linear relationship graph of ion concentration. DETAILED DESCRIPTION

[0036] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0037] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings.

[0038] Example 1

[0039] A method for preparing a Dy-MOF fluorescent probe material comprises the following steps:

[0040] Step 1: Weigh KOH (0.3 g, 5.3467 mmol) and dissolve it in 100 mL of deionized water to prepare a KOH solution.

[0041] Step 2, at room temperature, weigh the ligand HL (0.0216 g, 0.10 mmol), add the above 1.86 mL KOH solution and 2 mL MeOH to obtain a yellow clear solution.

[0042] Step 3, at room temperature, a solution of Dy(NO3)3·5H2O (0.0438 g, 0.10 mmol) dissolved in 2 mL of H2O was slowly added dropwise to the above yellow solution to obtain an orange-yellow transparent solution, which was stirred for 45 min and evaporated at room temperature for 6 days to obtain light yellow needle-like crystals.

[0043] Step 4: Filter the yellow needle-shaped crystals obtained above with a filter membrane with a pore size of 22 μm and use 6 mL (V H2O :V DMF =3:2) washed twice with deionized water and DMF, dried at 60° C. for 12 hours, cooled to room temperature, and ground using an agate mortar for 1 hour to obtain a Dy-MOF fluorescent probe material with a yield of 74.6%.

[0044] Example 2

[0045] A method for preparing a Dy-MOF fluorescent probe material comprises the following steps:

[0046] Step 1: Weigh KOH (0.3 g, 5.3467 mmol) and dissolve it in 100 mL of deionized water to prepare a KOH solution.

[0047] Step 2, at room temperature, weigh the ligand HL (0.0216 g, 0.10 mmol), add the above 2.0 mL KOH solution and 2 mL MeOH to obtain a yellow clear solution.

[0048] Step 3, at room temperature, slowly add the solution obtained by dissolving Dy(NO3)3·5H2O (0.0438 g, 0.10 mmol) in 2 mL of H2O to the above yellow solution to obtain an orange-yellow transparent solution, stir for 30 min, and evaporate at room temperature for 5 days to obtain light yellow needle-shaped crystals.

[0049] Step 4: Filter the yellow needle-shaped crystals obtained above with a filter membrane with a pore size of 22 μm and use 6 mL (V H2O :V DMF =1:1) deionized water and DMF were washed twice, dried at 70°C for 12 hours, cooled to room temperature, and ground using an agate mortar for 1 hour to obtain a Dy-MOF fluorescent probe material with a yield of 72.9%.

[0050] Example 3

[0051] A method for preparing a Dy-MOF fluorescent probe material comprises the following steps:

[0052] Step 1: Weigh KOH (0.3 g, 5.3467 mmol) and dissolve it in 100 mL of deionized water to prepare a KOH solution.

[0053] Step 2, at room temperature, weigh the ligand HL (0.0216 g, 0.10 mmol), add the above 2.2 mL KOH solution and 2 mL MeOH to obtain a yellow clear solution.

[0054] Step 3, at room temperature, a solution of Dy(NO3)3·5H2O (0.0657 g, 0.15 mmol) dissolved in 2 mL of H2O was slowly added dropwise to the above yellow solution to obtain an orange-yellow transparent solution, which was stirred for 60 min and evaporated at room temperature for 7 days to obtain light yellow needle-like crystals.

[0055] Step 4: Filter the yellow needle-shaped crystals obtained above with a filter membrane with a pore size of 22 μm and use 6 mL (V H2O :V DMF =2:1) ​​deionized water and DMF were washed twice, dried at 70°C for 10 hours, cooled to room temperature, and ground in an agate mortar for 30 minutes to obtain a Dy-MOF fluorescent probe material with a yield of 71.7%.

[0056] Example 4

[0057] A method for preparing a Dy-MOF fluorescent probe material comprises the following steps:

[0058] Step 1: Weigh KOH (0.3 g, 5.3467 mmol) and dissolve it in 100 mL of deionized water to prepare a KOH solution.

[0059] Step 2, at room temperature, weigh the ligand HL (0.0216 g, 0.10 mmol), add the above 2.5 mL KOH solution and 2 mL MeOH to obtain a yellow clear solution.

[0060] Step 3, at room temperature, a solution obtained by dissolving Dy(Cl)3·6H2O (0.0565 g, 0.15 mmol) in 2 mL of H2O was slowly added dropwise to the above yellow solution to obtain an orange-yellow transparent solution. After stirring for 60 min, the solution was evaporated at room temperature for 6 days to obtain light yellow needle-like crystals.

[0061] Step 4: Filter the yellow needle-shaped crystals obtained above with a filter membrane with a pore size of 22 μm and use 6 mL (V H2O :V DMF =1:1) deionized water and DMF were washed twice, dried at 60°C for 12 hours, cooled to room temperature, and ground using an agate mortar for 1 hour to obtain a Dy-MOF fluorescent probe material with a yield of 73.6%.

[0062] Performance test experiment

[0063] 1. The Dy-MOF fluorescent probe material prepared in the above-mentioned Example 1 of the present invention is subjected to X-ray single crystal diffraction analysis. The analysis shows that Dy-MOF crystallizes in the triclinic Pī space group with Z=2. Figure 1 It can be seen that in this MOF, L - The ligand ions adopt two coordination modes: monodentate coordination and μ2-κO:κO' bridging coordination mode. - Bridge L - Under the action of ligand ions, the adjacent Dy 3+ The ions are connected to form a one-dimensional chain structure.

[0064] 2. Perform infrared spectroscopy analysis on the Dy-MOF fluorescent probe material prepared in Example 1 of the present invention. Figure 2 As shown, 3600-3000cm -1 The absorption peaks between 3000-2800cm -1 The characteristic peak at 1680-1580cm -1 The characteristic peak at V as (COO - ) C=O peak, 1300cm -1 It is the characteristic peak of CO on the carboxyl group.

[0065] 3. The Dy-MOF fluorescent probe material prepared in Example 1 of the present invention was subjected to X-ray powder diffraction analysis. Figure 3 It can be seen that Dy-MOF exhibits good phase purity, which is basically consistent with the simulation peak.

[0066] 4. The Dy-MOF fluorescent probe material prepared in Example 1 of the present invention was subjected to thermogravimetric analysis. Figure 4 It can be seen that Dy-MOF exhibits good thermal stability, with a rapid weight loss of 7.90% in the range of 0-114°C and a weight loss of 9.37% at 349°C. According to the chemical formula of the complex [Dy(L)3(H2O)3] n ·2nH2O calculation, equivalent to 3 coordinated H2O molecules and 2 crystalline H2O molecules (theoretical value is 10.02%), indicating that up to 349℃, the one-dimensional polymer chain of MOF is still stable, showing good thermal stability. The weight loss in the range of 349-735℃ is 71.30%, which is equivalent to 3 ligands L - ions (theoretical value is 72.16%), and the remaining 19.33% by weight is Dy2O3 (theoretical value is 20.77%).

[0067] 5. The Dy-MOF fluorescent probe material prepared in Example 1 of the present invention is subjected to fluorescence emission spectrum detection. Figure 5 As shown, the maximum emission wavelength of the Dy-MOF fluorescent probe material prepared in Example 1 is 330 nm.

[0068] 6. The Dy-MOF fluorescent probe material prepared in Example 1 of the present invention was subjected to a fluorescence detection experiment to detect 21 common nitrates M(NO3) x The fluorescent probe selectivity experiment was carried out for monovalent, divalent or trivalent metal cations (M = Cu, Ba, Na, Ca, Ni, Zn, Pb, K, Dy, Fe, Hg, Co, Mn, Cr, Sr, Cd, Sm, Ce, Yb, La and Er; x = 1, 2 and 3). The specific steps are as follows: 0.1 mmol of Dy-MOF was dispersed in 10 mL of H2O and ultrasonically vibrated for 30 minutes to form a uniform suspension. Then the above metal salts were prepared into a concentration of 5×10 -3 mol / L aqueous solution, and then 1mL of the above nitrate solution was added to 2mL of Dy-MOF suspension, ultrasonicated for 30s and then allowed to stand for five minutes, and the fluorescence emission spectrum of the suspension was tested and studied. Figure 6 The fluorescence intensity comparison chart after adding various ions shows that when Cr 3+ After addition, the fluorescence response intensity of Dy-MOF was significantly weakened, while the addition of other analyte solutions had little effect on the fluorescence intensity of Dy-MOF, indicating that the Dy-MOF fluorescent probe material has a strong affinity for Cr. 3+ The selectivity is higher. Figure 7 Different concentrations of Cr 3+ From the fluorescence response spectrum of Cr 3+ As the solution concentration increases, the emission intensity of the Dy-MOF fluorescent probe material continues to weaken.

[0069] 7. The Dy-MOF fluorescent probe material prepared in Example 1 of the present invention was subjected to anti-interference experimental analysis. The specific steps are as follows: 0.1 mL of Cr was added to 2 mL of Dy-MOF suspension (1 mg / mL). 3+ ion solution (0.05 mol / L), and then add the above different metal nitrate solutions with the same concentration (0.05 mol / L, 0.1 mL), and measure their fluorescence emission spectra. Figure 8 As shown, in Cr 3+ In the presence of Cr in water, the addition of other metal ions has little effect on the fluorescence response intensity of Dy-MOF, indicating that Dy-MOF is sensitive to Cr in water. 3+ The detection has good anti-interference performance.

[0070] 8. The Dy-MOF fluorescent probe material prepared in Example 1 was subjected to a fluorescence detection test. The relative fluorescence intensity ratio (I0 / I)-1 and Cr 3+ The relationship between the concentration of can be described by the Stern-Volmer (SV) equation, I0 / I = 1 + K sv ×[C], where I0 represents the initial fluorescence intensity of Dy-MOF, and I represents the fluorescence intensity of Dy-MOF at different Cr 3+ Fluorescence intensity at ion concentration, K sv is the fluorescence quenching constant, [C] is Cr 3+ Ion concentration. Fig. 9 As shown, the fluorescence relative intensity ratio (I0 / I)-1 and C Cr3+ The linear relationship is between 0 and 0.35 mM, indicating that it can quantitatively detect Cr in water at low concentrations. 3+ Ion, K sv (Cr 3+ )=11.45728mM -1 (approximately 1.15×10 4 M -1 ), R 2 =0.98653, the detection limit can be calculated by the formula LOD = 3σ / k, where σ represents the standard deviation of the fluorescence intensity of ten blank samples, which is 0.4435, and k represents the linear slope, which is 1.15×10 4 M -1 The detection limit was calculated to be 1.16×10 -4 M.

[0071] In summary, the present invention designs and synthesizes a new type of Dy-MOF fluorescent probe material for Cr in water. 3+ The detection not only has a fast detection speed, but also shows strong sensitivity, selectivity and anti-interference. In addition, the preparation method of the Dy-MOF fluorescent probe material is simple, low in cost, low in pollution and easy to operate.

[0072] The above-described embodiments are only preferred experimental schemes of the present invention. It should be pointed out that for those skilled in the art, the experimental schemes have different ways of expression, which can be appropriately modified on the basis of the embodiments of the present invention, but they are all within the protection scope of the present invention.

Claims

1. A Dy-MOF fluorescent probe material, characterized in that: Its structural formula is: [Dy(L)3(H2O)3] n ·2nH2O, L in the structural formula - =4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid anion; in the triclinic system with Z=2 P It crystallized in space group ī with unit cell parameters: a=10.060(10) Å, b=10.193(10) Å, c=19.647(19) Å, α=85.172(19)°, β=76.808(17)°, γ=82.862(18)°.

2. The method for preparing the Dy-MOF fluorescent probe material according to claim 1, characterized in that: The following steps are involved: (i) Separately measure deionized water and KOH, and mix them to prepare a KOH solution; (ii): Weigh the ligand 4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid, add it to the KOH solution and methanol prepared in step (i), dissolve and stir to obtain a yellow clear solution; (iii): at room temperature, dissolving dysprosium salt in deionized water, and then slowly adding it dropwise to the yellow clear solution of step (ii) to obtain an orange-yellow transparent solution, which evaporates at room temperature to obtain light yellow needle-shaped crystals; (iv) filtering, washing, drying and grinding the light yellow needle-shaped crystals obtained in step (iii) to obtain a Dy-MOF fluorescent probe material; The molar ratio of the ligand 4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid to the dysprosium salt is 3:2 to 2:

3.

3. The method for preparing the Dy-MOF fluorescent probe material according to claim 2, characterized in that: The molar ratio of the ligand 4-(3,5-dimethyl-1H-pyrazol-1-yl)benzoic acid to KOH is 1:1~1:1.

5.

4. The method for preparing the Dy-MOF fluorescent probe material according to claim 2, characterized in that: The mass fraction of the solute in the KOH solution in step (i) is 0.3%.

5. The method for preparing the Dy-MOF fluorescent probe material according to claim 2, characterized in that: The dissolving and stirring time in step (ii) is 30 to 60 minutes.

6. The method for preparing the Dy-MOF fluorescent probe material according to claim 2, characterized in that: The dysprosium salt in step (iii) is any one of dysprosium nitrate pentahydrate or dysprosium chloride hexahydrate.

7. The method for preparing the Dy-MOF fluorescent probe material according to claim 2, characterized in that: The pore size of the filter membrane used in the filtration described in step (iv) is 22 μm; And / or, the solvent used for washing in step (iv) is a mixed solution of deionized water and DMF in a volume ratio of 1:1 to 3:1, and the washing times are 2 to 3 times; And / or, the drying temperature in step (iv) is 60-80°C and the drying time is 8-12h; And / or, the grinding in step (iv) is grinding using an agate mortar for 30 to 60 minutes.

8. The use of the Dy-MOF fluorescent probe material according to claim 1, characterized in that: The Dy-MOF fluorescent probe material is used to detect Cr in water 3+ .

9. The use of the Dy-MOF fluorescent probe material according to claim 8, characterized in that: The following steps are involved: The Dy-MOF fluorescent probe material is ground, dispersed in deionized water, and prepared into a suspension by ultrasonic treatment, and then a Cr-containing 3+ The liquid sample to be tested is then excited for fluorescence and the wavelength of the fluorescence emission is tested and analyzed.

10. The use of the Dy-MOF fluorescent probe material according to claim 9, characterized in that: The Dy-MOF fluorescent probe material is ground into 60-80 mesh; Dy-MOF is prepared into a suspension with a concentration of 0.01M; the ultrasonic treatment time is 30-60min; The Cr-containing 3+ The concentration of the liquid sample to be tested is 0~0.36mM; the Cr 3+ The liquid sample to be tested is ultrasonically dissolved with chromium nitrate and deionized water for 30 to 60 minutes to obtain a chromium nitrate solution.

Citation Information

Patent Citations

  • Europium metal-organic framework compound with fluorescent recognition function and preparation method and application

    CN105503915A

  • Rare-earth organic frame crystal material as well as preparation method and application thereof

    CN108164715A